The historical anthropology of intellectuals - Slapšak, Svetlana (Monitor ISH, 2007)
The history of intellectuals demands a special approach and methodology within historical anthropology. The objective of the research is thus an innovation in terms of both theme and methodology. The paper will examine the origins of the structures of thought which formed "intellectuals" as a separate group, as well as follow the development of socially and culturally productive narratives. The research is oriented toward aetiology and continuity, but has no ambition to offer a panorama or an overview of the historical features.
Keywords: intelektualci; zgodovinska antropologija; spol; ideologija; democracy; demokracija; raziskave